Pelayanan Terpadu Surat Izin Mengemudi (SIM) Terintegrasi - Putu Butsi Triyanti, Desak (Jurnal Ilmiah Administrasi Publik, 2016)
The process of making SIM in Indonesia have changed, such as more practical, transparent and accountable. Integrated Services in the driver's license at Resort Police Traffic Unit in Indonesia from procedure point of view has already meet the customer expectation, because nowadays the implementation of SIM manufacture is simple and clear. In term of service has also been running fairly because the services provided to all people regardless of their social status or the degree of the service request, In addition to existing services products contributing factor in the ability and skills of service personnel in the work should be carefully and thoroughly and services inhibiting factor is the lack of supporting facilities such as frequent disruptions internet service connection and the power outage situation.